Faal Paru Difusi : [Lung Diffusion: A Review] - Alfian Nur Rosyid; Isnin Anang Marhana (Faculty of Medicine Universitas Airlangga, 2018)
Diffusion capacity is useful for measuring ability of pulmonary microcirculation to transfer oxygen and carbon dioxide from alveoli to capillaries. Physiological examination of diffusion is a continuation of physiological examination of ventilation. Diffusion capacity is measured by DLCO (Diffusing capacity for Carbon Monoxide). Measurement of oxygen diffusion capacity directly is very difficult so that indirect methods are used using carbonmonoxide (DLCO). Diffusion capacity of oxygen is equivalent to DLCO multiplied by 1.23. Normal value of DLCO is 20-30 ml/minute mmHg. Some factors that affect DLCO are Hb levels, COHb in smokers, and alveolar volume. Some techniques for measuring DLCO include Steady-state, Three-equation Single-breath, Nitrogen Washout, and Intra-breath DLCO. This test is indicated in pulmonary parenchymal disease (pulmonary fibrosis, asbestosis, sarcoidosis, interstitial lung disease), cystic fibrosis, pulmonary hypertension, and pulmonary bleeding. DLCO is increased in asthma patients, obesity, polycythemia, intraalveolar bleeding, and right-left heart shunting. DLCO is decreased in emphysematous lung patients, pulmonary post resection, bronchial obstruction, multiple pulmonary embolism, anemia, idiopathic pulmonary fibrosis, asbestosis, sarcoidosis, vascular collagen disease, hypersensitive pneumonitis, and alveolar proteinosis.